PENERAPAN NILAI-NILAI RELIGUS DALAM MEMBANGUN PENDIDIKAN ISLAM PADA SISWA DI MI NU HIDAYATUN NAJAH - Akhmad Zaini (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Education is an effort made by someone with the aim of changing behavior, knowledge and character after taking it. Religious education is intended to increase religious potential and shape students to become human beings who believe and fear God Almighty and have noble character which includes ethics, character, and morals as the embodiment of religious education. Legislative values seen from this study at MI NU Hidayatun Najah include; the value of worship, the value of jihad, the value of morality, and the value of exemplary. The purpose of the study was to determine the forms of application of religious values to students. This study uses a qualitative approach research with a descriptive method which is to describe or interpret the situation regarding the conditions to be studied using words instead of numbers. The data collection technique in this study used observation and interview methods to observe the process of instilling the value of religiosity in students. The results of this study are shown in the pattern of application of religious values and the forms of application carried out in the environment by exposing the forms of worship values, jihad values, moral values, and exemplary values to students.